Forced adaptations of sporting behaviours during the Covid-19 pandemic and their effects on subjective well-being. (19th February 2021) - Mutz, Michael
ABSTRACT: Few studies have shown that exercise withdrawal and forced inactivity lead to negative mood states and increased symptoms of depression. Involuntary inactivity has become reality for millions during the Covid-19 pandemic, as mitigation and containment policies included the closings of sports facilities and leisure infrastructures. Based on representative survey data from Germany (≥14 years, N = 1001), the paper addresses the changes in sport and exercise activities in the pandemic situation and their association with emotional well-being. Findings show a reduced level of emotional well-being in the German population during the Covid-19 pandemic. In particular, those individuals who stopped or considerably reduced their sport and exercise activities during the pandemic report a significant decline of well-being compared to the time before the pandemic. Individuals, who reduced sport and exercise due to external constraints, reported the largest decline in well-being. In contrast, the small group of individuals who intensified their sporting activities during the pandemic stands out with the most positive well-being levels. Irrespective of sport and exercise adaptations, findings additionally show that females report a steeper decline in well-being during the crisis compared to men.